2011
DOI: 10.4049/jimmunol.1100594
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Mediated Phosphatidylinositol 3-Kinase/Serine–Threonine Kinase Activation in APCs Leads to Programmed Death-1 Ligand Upregulation and Suppression of HIV-Specific CD8 T Cells

Abstract: Recent evidence demonstrates that HIV-1 infection leads to the attenuation of cellular immune responses, which has been correlated with the increased expression of programmed death 1 (PD-1) on virus-specific CD8+ T cells. PD-1 is induced upon T cell activation and its prolonged expression facilitates CD8+ T cell inhibitory signals when bound to its B7 family ligands, PD-L1/2, which are expressed on APCs. Importantly, early reports demonstrated that blockade of the PD-1/PD-L interaction by antibodies may help t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 52 publications
(83 reference statements)
1
27
0
Order By: Relevance
“…The dependence of PD-L1 translation on PI3K-AKT-mTOR activity is also observed during viral infections. In HIV-1-infected macrophages and dendritic cells, the viral protein Nef induces PD-L1 transcription by binding to the promoter but PD-L1 protein expression depends on active PI3K/AKT signaling (40). Our data indicate that multiple types of stimuli, including growth factors cytokines and oncogenes, converge at mTOR to increase PD-L1 expression.…”
Section: Discussionmentioning
confidence: 70%
“…The dependence of PD-L1 translation on PI3K-AKT-mTOR activity is also observed during viral infections. In HIV-1-infected macrophages and dendritic cells, the viral protein Nef induces PD-L1 transcription by binding to the promoter but PD-L1 protein expression depends on active PI3K/AKT signaling (40). Our data indicate that multiple types of stimuli, including growth factors cytokines and oncogenes, converge at mTOR to increase PD-L1 expression.…”
Section: Discussionmentioning
confidence: 70%
“…One possible mechanism is that Akt inhibitor sensitizes the Akt plekstrin homology (PH) domain binding to phosphatidylinositol (3,4,5)-trisphosphate (PIP3), which facilitates membrane localization of Akt and induces conformational change of Akt, making it more susceptible to kinase phosphorylation or less susceptible to phosphatase dephosphorylation 44 . A previous study has shown that human immunodeficiency virus can activate PI3K/Akt to up-regulate PD-L1 expression 45 . Further, it has been shown that PI3K/Akt regulates PD-L1 expression at post-transcriptional levels 46 .…”
Section: Discussionmentioning
confidence: 99%
“…PDL1 could be preferentially up-regulated in macrophages in an anti-inflammatory environment and PD-L2 might be predominantly up-regulated in a pro-inflammatory environment (Rodriguez-Garcia et al, 2011). HIV infection could also induce the expression of PD-L1 in DC (Muthumani et al, 2011). Additionally, PD-L1 overexpression has also been observed in T cell subsets of HIV infected individuals (Rosignoli et al, 2009), the mechanism by which this over-expression occurs remains poorly studied but, the over-expression of PD-1 ligands on T cells opens the possibility of a new T cell-T cell interaction that might be contributing to PD-1 upregulation.…”
Section: Ajidmentioning
confidence: 99%
“…The influence of the overexpression of these molecules on T cell functions has been clarified by using specific antibodies to block the interaction of PD-1 with its ligands (Finnefrock et al, 2009;Freeman et al, 2006). Blockade of the PD-1 pathway shows improvement in some T cell functions, enhances proliferation of HIV-specific CD4+ and CD8+ T cells and increases the secretion of some cytokines (Muthumani et al, 2011). Additionally, PD-1 expressed on monocytes might also be contributing to IL-10 production, which in turn favous T cell dysfunction (Said et al, 2010).…”
Section: Pd-1 and Its Ligands During Chronic Viral Infections Such Asmentioning
confidence: 99%
See 1 more Smart Citation